Boosting nitrogen reduction on single Mo atom by tuning its coordination environment. Issue 24 (16th November 2021) - Kong, Lingyi; Qiu, Siyao; Cai, Qinghai; Zhao, Jingxiang; Sun, Chenghua
Abstract : Through modulating various coordination combinations, a Mo-based SAC with a unique B, O-dual coordination (Mo-B3 O) was revealed to exhibit superior NRR catalytic activity. Abstract : Modulating the microenvironment of single-atom catalysts (SACs) has been identified as an effective strategy to improve their performance in electrocatalysis. Here, by means of comprehensive density functional theory (DFT) computations, we systematically explored the effects of the coordination environment on the catalytic activity of single Mo atoms towards the nitrogen reduction reaction (NRR) for ammonia synthesis. Through comparing a large series of coordination combinations, we found that the Mo-based SAC with a unique B, O-dual coordination (Mo-B3 O) exhibits the best NRR performance with ultralow limiting potential (−0.34 V), which preferably proceeds along the enzymatic pathway, with the initial hydrogenation (*N2 → *N2 H) as the potential-limiting step. Moreover, the Mo-B3 O can suppress the competing H2 production, exhibit high thermodynamic stability, and hold great promise for experimental synthesis. Our findings not only further enrich the family of SACs by controlling the local coordination, but also offer cost-effective opportunities for advancing sustainable NH3 production.